Effect of working fluid on selection of gas turbine cycle configuration for Gen-IV nuclear power plant system - Osigwe, Emmanuel O.; Gad-Briggs, Arnold; Pilidis, Pericles; Nikolaidis, Theoklis; Sampath, Suresh (JSME, 2019)
The cycle configuration of the energy conversion system in a nuclear power plant tends to have a governing effect on the overall performance and acquisition cost. Interestingly, one factor that could greatly affect the design choice of the cycle configuration which may not have been explored extensively in many literatures reviewed is the choice of the working fluid. This paper presents a technical analysis on the effect of working fluid on selection of the cycle arrangement for a Generation IV nuclear power plant. It provides insight on potential performance gains that justifies the benefit for an additional cost of a complex cycle, and how the working fluid can influence this choice. The study identifies candidate working fluid that may be suitable for simple, inter-cooled-recuperated, recuperated and other complex cycles. The results obtained shows that for fluid like carbon dioxide, its optimal performance is achieved above it critical points which will require pressurizing the system or operating at high pressure ratio, hence, it would be suitable for a re-compressed inter-cooled cycle configuration. Similar, for fluid like helium with low molecular weight and high gas properties, the simple cycle configuration seem more realistic for its highest cycle efficiency of 41% and turbomachinery design.
Keywords: Working Fluid; Closed-Cycle Gas Turbine; Cycle Performance; Technology Readiness; Generation IV Nuclear Reactors